2018
DOI: 10.1016/j.antiviral.2018.03.005
|View full text |Cite
|
Sign up to set email alerts
|

PrEP-001 prophylactic effect against rhinovirus and influenza virus - RESULTS of 2 randomized trials

Abstract: Study 1, HRV-A16 study: EudraCT Number 2012-005579-14 (study conducted before ClinicalTrials.gov registration required). Study 2, H3N2-IAV study: EudraCT Number 2015-002895-26 and ClinicalTrials.gov: NCT03220048.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…A modified poly I:C has been shown to be safe in Phase I trials in HIV-infected people on antiretroviral therapy ( Saxena et al, 2019 ). Also in clinical trial, a proprietary poly I:C vaccine administered IN was found to be effective in prevention of infection by rhinovirus and influenza A ( Malcolm et al, 2018 ). IN administration is preferred for some vaccines, eliciting better responses than intramuscular injection in some cases ( Hoft et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…A modified poly I:C has been shown to be safe in Phase I trials in HIV-infected people on antiretroviral therapy ( Saxena et al, 2019 ). Also in clinical trial, a proprietary poly I:C vaccine administered IN was found to be effective in prevention of infection by rhinovirus and influenza A ( Malcolm et al, 2018 ). IN administration is preferred for some vaccines, eliciting better responses than intramuscular injection in some cases ( Hoft et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Two PrEP-001 human clinical trials administering powdered poly(I:C) i.n. twice, 48 and 24 h prior to challenge with either rhinovirus or influenza A virus, showed reduced development of clinical illness and symptoms [10]. In another study, IFN-β-1a was i.n.…”
Section: Discussionmentioning
confidence: 94%
“…Modern pharmaceutical design and engineering has made it possible to synthetically design TLR agonists and, combined with novel delivery techniques, these can now be safely delivered to mucosal surfaces, which permits clinical testing. In recent clinical trials, intranasal delivery of the TLR3 agonist polyinosinic:polycytidylic acid [poly(I:C)], a synthetic dsRNA structurally similar to virus dsRNA, stimulated IFN-I production and significantly protected against Rhinovirus and Influenza virus infections in humans [10]. This immune prophylaxis was safe and well-tolerated.…”
Section: Introductionmentioning
confidence: 99%
“…Two PrEP-001 human clinical trials administering powdered poly(I:C) i.n. twice 48 and 24 h prior to challenge with either rhinovirus or influenza A virus showed reduced development of clinical illness and symptoms (10). In another study, IFNβ-1a was intranasally dosed once daily up to 14 days to patients hospitalized with Covid-19 symptoms, which was well tolerated and resulted in greater chances of recovery compared to a placebo group (24).…”
Section: Discussionmentioning
confidence: 99%
“…Modern pharmaceutical design and engineering has made it possible to synthetically design TLR agonists and, combined with novel delivery techniques, these can now be delivered safely to mucosal surfaces, which permits clinical testing. In recent clinical trials intranasal delivery of the TLR3 agonist polyinosinic:polycytidylic acid [poly(I:C)], a synthetic dsRNA structurally similar to virus dsRNA, stimulated IFN-I production and significantly protected against Rhinovirus and Influenza virus infections in humans (10). This immune prophylaxis was safe and well tolerated.…”
Section: Introductionmentioning
confidence: 99%